Technological market conjuncture: risk assessment commercialization of intellectual property - Kosenko, Aleksandra; Pererva, P. G. (University of Miskolc, 2014)
This paper deals with the determination of the risk assessment process in market conditions using the method of paired comparisons. The most important factors influencing the level of market appeal of intelligent technology are defined and stipulated. Recommendations are made for reducing the impact of risk factors in course of the commercialization of intellectual property.

У статті розглядається визначення процесу оцінки ризиків в умовах ринку з використанням методу парних порівнянь. Найбільш важливих факторів, що впливають на рівень привабливості ринку інтелектуальних технологій визначені і обумовлені. Рекомендації щодо зниження впливу факторів ризику в процесі комерціалізації інтелектуальної власності.
Кон'юнктура технологічного ринку: оцінка ризику комерціалізації інтелектуальної власності
Keywords: market conditions; risk; market technology; intellectual property; paired comparison; умови ринкові; ризики; технології ринкові; власність інтелектуальна